Heterostructuring Mesoporous 2D Iridium Nanosheets with Amorphous Nickel Boron Oxide Layers to Improve Electrolytic Water Splitting. Issue 10 (1st September 2021) - Kang, Yunqing; Jiang, Bo; Malgras, Victor; Guo, Yanna; Cretu, Ovidiu; Kimoto, Koji; Ashok, Aditya; Wan, Zhe; Li, Hexing; Sugahara, Yoshiyuki; Yamauchi, Yusuke; Asahi, Toru
Abstract: 2D heterostructures exhibit a considerable potential in electrolytic water splitting due to their high specific surface areas, tunable electronic properties, and diverse hybrid compositions. However, the fabrication of well‐defined 2D mesoporous amorphous‐crystalline heterostructures with highly active heterointerfaces remains challenging. Herein, an efficient 2D heterostructure consisting of amorphous nickel boron oxide (Ni‐B i ) and crystalline mesoporous iridium (meso‐Ir) is designed for water splitting, referred to as Ni‐B i /meso‐Ir. Benefiting from well‐defined 2D heterostructures and strong interfacial coupling, the resulting mesoporous dual‐phase Ni‐B i /meso‐Ir possesses abundant catalytically active heterointerfaces and boosts the exposure of active sites, compared to their crystalline and amorphous mono‐counterparts. The electronic state of the iridium sites is tuned favorably by hybridizing with Ni‐B i layers. Consequently, the Ni‐B i /meso‐Ir heterostructures show superior and stable electrochemical performance toward both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in an alkaline electrolyte. Abstract : This heterostructure is designed to maximize the contact area between the nickel boron oxide layer (Ni‐B i ) and the mesoporous iridium framework (meso‐Ir). The synergistic interactions taking place at these heterointerfaces provide abundant adsorption sites and improve the overall hydrophilicity. The Ni‐B i /meso‐Ir heterostructure can be used both as anode or cathode, showing superior electrochemical water splitting performance in alkaline electrolyte.